Metric power - Beer, David, author. 3645 1977- (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book examines the powerful and intensifying role that metrics play in ordering and shaping our everyday lives. Focusing upon the interconnections between measurement, circulation and possibility, the author explores the interwoven relations between power and metrics. He draws upon a wide-range of interdisciplinary resources to place these metrics within their broader historical, political and social contexts. More specifically, he illuminates the various ways that metrics implicate our lives - from our work, to our consumption and our leisure, through to our bodily routines and the financial and organisational structures that surround us. Unravelling the power dynamics that underpin and reside within the so-called big data revolution, he develops the central concept of Metric Power along with a set of conceptual resources for thinking critically about the powerful role played by metrics in the social world today. Chapter 1. Introducing metric power -- Chapter 2. Measurement -- Chapter 3. Circulation -- Chapter 4. Possibility -- Chapter 5. Conclusion: The intersections and imbrications of metric power -- Chapter 6. Coda... Metric power and the production of uncertainty.(how does metric power make us feel?). This book examines the powerful and intensifying role that metrics play in ordering and shaping our everyday lives. Focusing upon the interconnections between measurement, circulation and possibility, the author explores the interwoven relations between power and metrics. He draws upon a wide-range of interdisciplinary resources to place these metrics within their broader historical, political and social contexts. More specifically, he illuminates the various ways that metrics implicate our lives - from our work, to our consumption and our leisure, through to our bodily routines and the financial and organisational structures that surround us. Unravelling the power dynamics that underpin and reside within the so-called big data revolution, he develops the central concept of Metric Power along with a set of conceptual resources for thinking critically about the powerful role played by metrics in the social world today. Description based on publisher-supplied MARC data.